Doping effect in Si nanocrystals. (21st May 2018) - Li, Dongke; Xu, Jun; Zhang, Pei; Jiang, Yicheng; Chen, Kunji
Abstract: Intentional doping in semiconductors is a fundamental issue since it can control the conduction type and ability as well as modify the optical and electronic properties. To realize effective doping is the basis for developing semiconductor devices. However, by reducing the size of a semiconductor, like Si, to the nanometer scale, the doping effects become complicated due to the coupling between the quantum confinement effect and the surfaces and/or interfaces effect. In particular, by introducing phosphorus or boron impurities as dopants into material containing Si nanocrystals with a dot size of less than 10 nm, it exhibits different behaviors and influences on the physical properties from its bulk counterpart. Understanding the doping effects in Si nanocrystals is currently a challenge in order to further improve the performance of the next generation of nano-electronic and photonic devices. In this review, we present an overview of the latest theoretical studies and experimental results on dopant distributions and their effects on the electronic and optical properties of Si nanocrystals. In particular, the advanced characterization techniques on dopant distribution, the carrier transport process as well as the linear and nonlinear optical properties of doped Si nanocrystals, are systematically summarized.